Dendroclimatology using tropical broad-leaved tree species – a review - Fichtler, Esther (ERDKUNDE, 2017)
Global change has led to the warming of the atmosphere and oceans, the diminishment of snow and ice, while the sea level is rising. These changes have widespread impacts on human and natural systems on all continents and across the oceans. In tropical regions, ecosystems and socio-economic cultures become more and more affected by the high vulnerability to extreme climate events, deforestation and population growth. Therefore long term climate records from these regions are needed to better understand the natural climate variability and to simulate the magnitude of human-induced factors on climate change. However, climate records from tropical regions are scarce in time and space. Whenever tree growth is limited directly or indirectly by climate variables that can be quantified and dated, dendroclimatological methods can be used to reconstruct past environmental conditions - dendroclimatology examines the relationship between tree growth and climate with an annual resolution. Dendroclimatology in the tropics still remains in an early stage, although paleoclimatic records from tropical regions are essential to our understanding of past changes in the Earth’s climatic system, equator-to-pole linkages, and the prediction of sensitivity of tropical regions to future climate change. This review gives an overview on different aspects of tropical dendroclimatology on classical ring width studies in broad-leaved species, looking at two tropical biomes, moist broadleaf and dry broadleaf forests. It points to technical aspects of tropical dendrochronology and refers to a multitude of successful tree-ring studies of tropical species related to climate. This demonstrates that tropical dendroclimatology is undergoing a promising development; however, tropical tree-ring studies mainly take place in the dry tropics, while studies in the wet tropical forests are still the exception.